Efficacy and safety of peficitinib (ASP015K) in patients with rheumatoid arthritis and an inadequate response to conventional DMARDs: a randomised, double-blind, placebo-controlled phase III trial (RAJ3). Issue 10 (26th July 2019) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Tanaka, Sakae; Kawakami, Atsushi; Iwasaki, Manabu; Song, Yeong Wook; Chen, Yi-Hsing; Wei, James Cheng-Chung; Lee, Sang-Heon; Rokuda, Mitsuhiro; Izutsu, Hiroyuki; Ushijima, Satoshi; et al.
Abstract : Objectives: To investigate the efficacy and safety of peficitinib, an oral Janus kinase inhibitor, in patients with rheumatoid arthritis (RA). Methods: In this double-blind phase III study, patients with RA and an inadequate response to prior disease-modifying anti-rheumatic drugs (DMARDs) were randomised to peficitinib 100 mg once daily, peficitinib 150 mg once daily, placebo or open-label etanercept for 52 weeks' treatment; placebo-treated patients were switched at week 12 to peficitinib 100 or 150 mg once daily. The primary endpoint was American College of Rheumatology (ACR)20 response at week 12/early termination (ET). Secondary endpoints (assessed throughout) included ACR20, ACR50 and ACR70 response, changes from baseline in disease activity scores (DAS)28 and ACR core parameters, adverse events (AEs) and changes in clinical or laboratory measurements. Results: In total, 507 patients received treatment. ACR20 response rates at week 12/ET were significantly higher in the peficitinib 100 mg (57.7%) and 150 mg (74.5%) groups versus placebo (30.7%) (p<0.001). ACR50/70 response rates were also higher for both peficitinib doses versus placebo. Improvements in ACR response were maintained until week 52. Changes from baseline in DAS28-C-reactive protein/erythrocyte sedimentation rate and the ACR core set were significantly greater for both peficitinib doses versus placebo at week 12/ET (p<0.001). AE incidence was similar across treatment arms. Incidence of serious infection and herpes zoster-related disease was higher with peficitinib versus placebo, but with no clear dose-dependent increase. Conclusions: In patients with RA and inadequate response to DMARDs, peficitinib 100 mg once daily or 150 mg once daily was efficacious in reducing RA symptoms and was well tolerated compared with placebo. Trial registration number: NCT02308163 .